Twelve-week multimodal programs can improve dual-task performance in risk factors for falls in community-dwelling older adults: a pilot study. (24th June 2020) - Rosado, H; Bravo, J; Raimundo, A; Mendes, F; Pereira, C
Abstract: Introduction Performing a dual-task (DT), mainly while walking and performing another task simultaneously, is seen as determinants factors for falls and injuries in older adults. A psychomotor intervention relying on the prevention of sensorimotor and neurocognitive deterioration may prevent falls. The whole-body vibration (WBV) promotes the increase of agility, reducing the risk of falling. However, an intervention that combines both methods can lead to additional benefits, particularly as regards DT. Objectives To evaluate the feasibility and the effect of two multimodal programs designed for community-dwelling older adults, fallers or at high risk of falling, on DT performance ability. Methodology Thirty-seven participants (74.3±5.2 years) were randomly assigned into experimental group 1 [EG1] (psychomotor intervention); or experimental group 2 [EG2] (psychomotor intervention + WBV). DT performance (TUGcog) was assessed by the Timed Up and Go Test (s) performed simultaneously with the counting backward cognitive task. Results Adherence rate was 86.3%. Wilcoxon test comparisons showed improvements from baseline to post-intervention on EG1 (time (s): 10.1±2.7 vs. 9.0±2.7, p = 0.001; cognitive stops (n): 0.9±1.0 vs. 0.2±0.4, p = 0.012; motor stops (n): 0.3±0.5 vs. 0.0±0.0, p = 0.025), corresponding to an effect size (cohen's d) ranging from 0.41 (small) to 0.92 (medium) and on EG2 (time (s): 9.9±2.5 vs. 8.5±1.8, p = 0.010; cognitive stops (n): 1.1±0.7 vs. 0.4±0.5, p = 0.004), corresponding to a d ranging from 0.64 (medium) to 1.15 (medium). There were no significant differences between groups. Conclusion These preliminary results suggested that the multimodal programs were feasible and effective in reducing the risk of falling by improving the determinant risk factor DT performance. Trial Registration: ClinicalTrials.gov Identifier: NCT03446352. Funding: This study was funded by ESACA Project (Grant ALT20-03-0145-FEDER-000007) and by FCT (SFRH/BD/147398/2019).